Selective Laser Sintering of PMMA and PMMA Plus β-tricalcium Phosphate Polymer Composites - Velu, Rajkumar (Auckland University of Technology, 2017)
Certain material systems are currently playing significant roles in the medical application areas. Classified as bio-polymers, polyethylene (PE), polyamide (PA), Poly(ε-caprolactone) (PCL), poly (lactic acid) (PLA), poly (glycolic acid) (PGA), and poly (lactic-co-glycolic acid) (PLGA), poly (methyl methacrylate) (PMMA) are notable examples. While these materials are known for their bio-compatibility characteristics, the bio-conductive nature promoting further growth and repairing the damaged parts is often lacking. Natural coral derived HA/calcium carbonate composites and synthetic calcium phosphates are known for bio-conductivity. As a natural consequence, medical materials used in particular for bone repair and replacement needs are a mixture of a biopolymer composite and a bio ceramic. The resulting bio-polymer composites loaded with bio-ceramics such as hydroxyapatite and calcium phosphate into different bio-polymer matrices combine the properties both phases and serve the purpose of the specific medical application. Several processing methods such as solvent casting or leaching, phase separation, foaming, gas saturation etc., are applied to put these polymer composites to service. However, most methods fail due to several drawbacks such as time and cost involved and more importantly, lack of flexibility to exactly reproduce complex shapes. In particular, achieving a complex shape is often a prerequisite condition in many medical applications. During the past two decades, the layered processing methods rapidly evolved from mere prototyping solutions to the more advanced technologies, commonly referred to as additive manufacturing. Considering the freedom these techniques offer to manufacture complex forms without any specific tooling or the alteration of the materials and processes, it became important to revisit the current processing techniques as applied to different biopolymers used for varying medical needs. The current research is an attempt in this direction, evaluating a selected combination of a bio-material and an additive processing technology. The specific medical application area targeted is in the bone repair and replacement tasks. Poly (methyl methacrylate) (PMMA) is selected as the base polymer considering its wider use in bone related applications. The β-form of the tri-calcium phosphate (β-TCP) is the bio-ceramic component to impart the bio-conductivity to the polymer composite. Selective laser sintering is the process, considering the ease of working with powder raw materials and the ultimate control over the micro and meso structures of the sintered substrates. The material consolidation mechanism involves localized heating by a fast moving laser beam. The first task is to match the material combinations with the laser energy so that the substrates absorbs sufficient energy from the laser to achieve the particle melting, fusion, and consolidation. Considering the absorptivity levels of the constituent powders, a CO2 laser source is selected for the experimental investigations. Simulating the laser sintering process conditions required the development of both hardware and software systems and the integration of the same to achieve the overall experimental test bed. Powder feeding and envelope temperature control systems are added for further process controls. Establishing the viability of the material and process combination involved experimental evaluations in three significant stages. The neat PMMA powders are evaluated first for laser sintering with varying process parameters. Working ranges of laser energy densities for initial laser sintering experiments are established by differential scanning calorimetric results. Morphologies of sintered surfaces and porosity analyses are used to evaluate the intra-layer coalescence. Critical process parameters, laser power and scan velocities are gradually adjusted towards more optimum combinations based on these initial results. Further sintering trials and evaluation of the morphological, physical and mechanical characterization results allowed to establish the best process conditions and the overall effectiveness of neat PMMA for selective laser sintering. The same procedure is repeated in the second stage based on varying compositions of PMMA plus β-TCP composites. The final stage involved evaluation of the possible after-effects if any on the biological and the multi-layer responses of the sintered polymer composites based on Fourier transform infrared spectroscopy (FTIR), in-vitro analyses, and mechanical testing. Overall, the experimental results indicate the suitability of both neat PMMA and PMMA plus β-TCP polymeric materials for processing by selective laser sintering. Best combinations of critical process parameters, laser power and scan velocities could be established for both material systems. The laser interactions are proved to cause no detrimental effects either in the polymer chemistry or the biological nature of the materials further to sintering. Sufficient inter-layer coalescence is also evidenced, establishing the effectiveness of the material and process combination for manufacturing 3D forms. Considering the significant attributes of the constituent material systems and the unlimited design freedom allowed by the laser sintering approach, the findings reported in this thesis are expected to pave ways for wider research interest as well as potential medical applications in the future.
Keywords: Additive Manufacturing; PMMA; Tricalcium Phosphate; SLS